Developing Student Worskshet Based on Open Ended Problem to Improve Mathematical Problem Solving Abilities - Alawiyyah, Shifa; Arifuddin, Ahmad; Andini, Wulan (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2024)
This research focuses on developing student worksheets based open ended problem on the topic of dividing whole numbers. The aim of this development is to produce feasible and effective student worksheets. The research method used is research and development with the ASSURE development model. Data collection techniques include questionnaires and tests. The subjects of this research were 29 class III Madrasah Ibtidaiyah students. The research results showed that the media expert's score was 3.75 (very valid), the language expert's score was 3.44 (very valid), and the material expert's score was 3.56 (very valid). Based on the test scores for problem solving ability for dividing whole numbers, average results were obtained pretest 55.38 and posttest 70.14 there is an increase of 0.30 with moderate criteria. As well as from test results paired sample t-test obtained sig value. (2-tailed) is 0.000 < 0.05, so it can be concluded that open-ended problem-based student worksheets media is declared effective in improving students' problem-solving abilities. So that student worksheets media is based open ended problem This has met the valid and effective criteria so it can be used in the learning process. Keywords: Student Worksheets; Problem Solving Ability